Atividade de enzimas relacionadas ao processo de ossificação em girinos de Lithobates catesbeianus - Colósio, Rafael Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Biological calcification is a tight regulated process in which different types of tissues, cells, organelles, and biomolecules participate in the coordination and regulation of metabolic events involved in accumulating calcium phosphate, in the form of hidroxiapatite crystals. The morphological changes that occur during anuran metamorphosis are extremely accentuated and perceptible, such as the remodeling of the skeleton. The ossification events are rarely described for tadpoles in the literature. The tartarate resistant acid phosphatase has been widely used as a specific marker of osteoclasts, cells that participate in the process of resorption and remodeling of bone tissue, while the alkaline phosphatase has been used as a marker for osteoblasts, cells responsible for bone tissue formation. Studies conducted by many researchers with the aim of determining, mainly, the enzymes in chondrocyte extracellular vesicles have revealed the presence of other enzymes, in addition to alkaline phosphatase, which are important to the process of biological calcification. Thus, in the present study, the changes in the activity of phosphatases in the ossification process during the development of the limbs of Lithobates catesbeianus was evaluated, with the aim to contribute to the understanding of this process not only in anurans, but also in other vertebrates. The animals were desensitized in water with ice, decapitated and limb bones were removed and homogenized, centrifuged, and the supernatant aliquoted, frozen in liquid nitrogen and stored at -70ºC for subsequent enzymatic activities and protein quantification. The enzymes, acid phosphatase and alkaline phosphatase, remained stable in all of the studied storage pH, the apparent pH optimum of hydrolysis of p-nitrophenyl phosphate (PNPP) was of 5.0 and 10.5, respectively, and the enzymes were stable at 45ºC and the t1/2 was 60 minutes at 55ºC for alkaline...

A calcificação biológica é um processo muito bem regulado, no qual os diferentes tipos de tecidos, células, organelas e biomoléculas, participam na coordenação e regulação de eventos metabólicos envolvidos na deposição de fosfato de cálcio, sob a forma de cristais de hidroxiapatita. As alterações morfológicas ocorridas nos anuros, durante a metamorfose, são extremamente acentuadas e perceptíveis, sendo uma delas a remodelação do esqueleto. Os eventos relacionados à ossificação em girinos raramente são descritos na literatura. A fosfatase ácida tartarato resistente tem sido amplamente utilizada como um marcador específico de osteoclastos, células que participam do processo de reabsorção e de remodelação do tecido ósseo, enquanto a fosfatase alcalina tem sido usada como marcador de osteoblastos, células responsáveis pela formação do tecido ósseo. Estudos efetuados por vários pesquisadores, com o objetivo de determinar, principalmente, as enzimas presentes nas vesículas extracelulares dos condrócitos, têm revelado a presença de outras enzimas, além da fosfatase alcalina que são importantes para o processo de calcificação biológica. Assim, no presente trabalho foi avaliada a variação na atividade das fosfatases no processo de ossificação no período de desenvolvimento dos membros de Lithobates catesbeianus, a fim de contribuir na compreensão deste processo não somente em anuros, mas também nos demais vertebrados. Os animais foram dessensibilizados em água com gelo, decapitados, os membros foram removidos, em seguida os ossos foram descarnados e homogeneizados, centrifugados, sendo o sobrenadante aliquotado, congelado em nitrogênio líquido e armazenado a -70ºC para posteriores atividades enzimáticas e dosagem de proteína no extrato. As enzimas, fosfatase ácida e fosfatase alcalina, apresentaram estabilidade em todos os pH de armazenamento estudados...
Keywords: Calcificação; Osteoblastos; Fosfatases; Metamorfose; Rã touro; Bullfrog